Ação antifúngica dos óleos essenciais de Origanum vulgare e Rosmarinus officinalis frente a isolados de Pythium insidiosum e Dermatófitos - Fonseca, Anelise Oliveira da Silva (2011)
This study aimed to determine the chemical composition and evaluate the antifungal essential oils of Origanum vulgare (oregano) and Rosmarinus officinalis (rosemary). The oils were analyzed by gas chromatography and identified by comparison with the retention time of standards. To evaluate the antifungal activity method was used in broth, and used nine isolates of dermatophytes and nine isolates of Pythium insidiosum from clinical cases in animals. The oils were subjected to a series of ten dilutions in logarithm base 2, in RPMI 1640, resulting in concentrations from 30 to 0, 03 μlmL-1. The microplates were incubated at 32°C for 72 h and susceptibility was expressed by the minimum inhibitory concentration (MIC). The main oil constituents R. officinalis were camphor (51.52%), verbenone (11.84%), 1,8-cineole (8.94%), myrcene (4.50%), α-terpineol (4.39%) and borneol (2.68%) and O. vulgare were 4-terpineol (27.67%), gamma-terpinene (4.10%), thymol (0.58%) and carvacrol (21.58%). For dermatophytes the MIC R. Officinallis ranged from 30 to 3 μ/lmL and O. vulgare varied from 3 to 0.3 μL/ml. In the case of P. insidiosum MIC R. Officinallis ranged from 3 to 1.5 μl/mL and O. vulgare varied from 3 to 0.75 μl/mL. According to the results obtained, it can be argued that the tested oils have antifungal activity on dermatophytes and P. insidiosum. The results should stimulate further research, especially in relation to P. insidiosum, as yet no effective treatment is available.